Efikasi Terapi Empagliflozin pada Pasien Gagal Jantung Akut: Meta-analisis - Pintaningrum, Yusra; Pranayoga, Komang (Postgraduate, University of Mataram, 2023)
Heart failure is still a common disorder with a high morbidity and mortality rate around the world. New drugs sodium-glucose cotransporter 2 inhibitors (SGLT2i) such as empagliflozin are currently showing promising results across the HF spectrum. Based on this, the authors are interested in researching the efficacy of Empaglifozin Therapy in Patient with Acute Heart Failure. This study used a systematic search using PRISMA principle in several online databases (Pubmed, Cochrane library and Google scholar). The selected study was an RCT or clinical trial with a population of Acute HF patients. The intervention group is Empagliflozin in any dose compared to placebo. The primary outcome for this meta-analysis is the levels of BNP or NT-proBNP and mortality after intervention. Selected study will be assessed and analyzed using Review Manager software version 5.3 with 95% CI. The two studies selected in this meta-analysis had a total sample size of 290 in the intervention group and 285 in the placebo group. Heterogenecity test obtained [p=0.44; I2 0%], indicating the homogenous data and the study is recommended to use the fixed effect method. The pooled effect size of RR is 0.472 [CI95% 0.24-0.75, P=0.003], meaning that there is a significant favorable outcome in empagliflozin group than in the placebo group. The results showed that empagliflozin had shown a favorable effect in reduction of the risk of death and reducing level of NT-proBNP in patient with acute heart failure.